A Contrastive Psycholinguistic Study of the British Emotional Concept ’Envy’ and Ukrainian ’Zazdrist’’: Particularities of Phraseological Objectification - Mizin, Kostiantyn; Slavova, Liudmyla; Petrov, Oleksandr (East European Journal of Psycholinguistics, 2021)
The article focuses on exploring the phraseological objectification of the “sinful” emotional concepts Brit. ENVY and Ukr. ЗАЗДРІСТЬ in the remotely related lingual cultures (British and Ukrainian). To identify common and distinctive senses of these concepts (1) the range of the concepts that closely correlate to the discussed emotional concepts was defined and (2) the system of conceptual metaphors representing these concepts was revealed. The material involves 253 phraseological units (PUs) that denote envy in the English language and 309 PUs in Ukrainian. The material is selected from authoritative explanatory, bilingual and phraseological dictionaries. The contrastive research of the concepts ENVY & ЗАЗДРІСТЬ that correlate with other ethical and emotional concepts (e.g.: GRATITUDE, KINDNESS, VIRTUE, HONOUR) makes it possible to speak about the concurrence of fundamental moral values and attitudes in Christian cultures. Moreover, the concepts ENVY & ЗАЗДРІСТЬ figure prominently in the hierarchy of values (“white” envy) vs. disvalues (“black” envy) of the contrasted lingual cultures. The conceptual metaphors provide the concept ENVY with the meanings that are considered to be specific for the lingual culture under study. Our findings show that despite the universal character of envy both as an emotion and a feeling, it is permanently affected by ethnic and socio-cultural factors that provide the concepts ENVY & ЗАЗДРІСТЬ with specific lingual cultural meanings. It is noteworthy that the study of the PUs can reveal only the traditional (fixed) understanding of envy. Therefore, to detect the changes in the modern priorities of the British and Ukrainians, it is necessary for prospective research to compare the results of the language material (lexicographic and phraseographic resources) with the results of analysis of actual language data, i.e. psycholinguistic experiments, sociolinguistic monitoring, language corpora.